1992
DOI: 10.1002/j.1460-2075.1992.tb05093.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin V gene replacement is caused by the intramolecular DNA deletion mechanism.

Abstract: Circular DNA resulting from V gene replacement was studied with an A‐MuLV transformed cell line containing ablts. This cell line undergoes V gene replacement at elevated temperatures in the immunoglobulin (Ig) heavy chain (H) gene. Examination of circular DNA revealed that a heptamer‐related sequence (TACTGTG) within the coding region of VDJ was joined to the recombination signal sequence (RSS) of a germline VH segment. This provides direct evidence for a intramolecular DNA deletion mechanism for V gene replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 40 publications
3
22
0
Order By: Relevance
“…Although Usuda et al [37] observed another form of such rearrangement in vivo which involved cryptic RSS in the switch regions of the constant region genes, this recombination seems to be related to class switching rather than V region gene rearrangement. Moreover, two cases of VH to VHDHJH rearrangement in human, which apparently occurred in vivo, were fortuitously rescued as a B lymphoma cell line or as a PCR product from leukemic patients [41, 421. In contrast, heterozygous T15i mutant mice provide us with a system where V region gene rearrangement involving cryptic RSS takes place constantly in vivo.…”
Section: Uniqueness Of T15i Mutant Mice In the Study Of The V Region mentioning
confidence: 91%
“…Although Usuda et al [37] observed another form of such rearrangement in vivo which involved cryptic RSS in the switch regions of the constant region genes, this recombination seems to be related to class switching rather than V region gene rearrangement. Moreover, two cases of VH to VHDHJH rearrangement in human, which apparently occurred in vivo, were fortuitously rescued as a B lymphoma cell line or as a PCR product from leukemic patients [41, 421. In contrast, heterozygous T15i mutant mice provide us with a system where V region gene rearrangement involving cryptic RSS takes place constantly in vivo.…”
Section: Uniqueness Of T15i Mutant Mice In the Study Of The V Region mentioning
confidence: 91%
“…At present, this is difficult to answer, because without specific molecular probes (3,20,21,32,38,57,72) or a strong phenotypic selection (2,11,26,27), cryptic rearrangements in a normal T-and B-cell population are effectively invisible. One would expect that natural selection has long since eliminated cryptic signals with a high probability of activating an oncogene through site-specific rearrangement.…”
Section: V(d)j Recombination Is An Obligatory Part Of T-and B-cell Dementioning
confidence: 99%
“…24,25 In the past, some studies have suggested an association between oligoclonality and both poor outcome 13 and higher WBC, 26 not confirmed in recent studies. Two principle mechanisms have been implicated in the occurrence of multiple IGH gene rearrangements in ALL: (1) the persistent activity of the recombinase machinery in the immature B cells in ALL; [28][29][30] and (2) duplication of chromosome 14 (involving the chromosome band 14q32, the locus harboring the IGH) 13 although the link between these two events has not been fully explored to date. The former results in VH replacement to VNDNJ pre-existing rearrangements 31,32 or in an 'open-and-shut' VDJ modification as previously described in ALL patients.…”
Section: Introductionmentioning
confidence: 99%